Behavioral and Cellular Pharmacology Characterization of 17-cyclopropylmethyl-3,14β-dihydroxy-4,5α-epoxy-6α-(isoquinoline-3′-carboxamido)morphinan (NAQ) as a Mu Opioid Receptor Selective Ligand - Zhang, Yan (2014)
Mu opioid receptor (MOR) selective antagonists and partial agonists have been used for the treatment of opioid abuse and addiction. Our recent efforts on the identification of MOR antagonists have provided several novel leads displaying interesting pharmacological profiles. Among them, 17-cyclopropylmethyl-3,14β-dihydroxy-4,5α-epoxy-6α-[(3'-isoquinolyl)acetamido]morphinan (NAQ) showed sub-nanomolar binding affinity to the MOR with significant selectivity over the delta opioid receptor (DOR) and the kappa opioid receptor (KOR). Its central nervous system penetration capacity together with marginal agonism in the MOR–GTPγS binding assay made it a very interesting molecule for developing novel opioid abuse and addiction therapeutic agents. Therefore, further pharmacological characterization was conducted to fully understand its biological profile. At the molecular and cellular level, NAQ not only induced no translocation of β-arrestin2 to the MOR, but also efficaciously antagonized the effect of DAMGO in MOR-βarr2eGFP-U2OS cells in the β-arrestin2 recruitment assay. At the in vivo level, NAQ displayed a potent inhibition of the analgesic effect of morphine in the tail-flick assay (ID(50) = 1.19 mg/kg). NAQ (10 mg/kg) also significantly decreased the hyper-locomotion induced by acute morphine without inducing any vertical jumps. Meanwhile NAQ precipitated lesser withdrawal symptoms in morphine dependent mice than naloxone. In conclusion, NAQ may represent a new chemical entity for opioid abuse and addiction treatment.